OPTIMIZATION OF MICROWAVE AND AIR DRYING CONDITIONS OF QUINCE (CYDONIA OBLONGA, MILLER) USING RESPONSE SURFACE METHODOLOGY - Cem Baltacioglu (Italian Journal of Food Science, 2015)
Effects of slice thickness of quince (Cydonia oblonga Miller) , microwave incident power and air drying temperature on antioxidant activity and total phenolic content of quince were investigated during drying in microwave and air drying. Optimum conditions were found to be: i) for microwave drying, 285 W and 4.14 mm thick (maximum antioxidant activity) and 285 W and 6.85 mm thick (maximum total phenolic content), and ii) for air drying, 75 ºC and 1.2 mm thick (both maximum antioxidant activity and total phenolic content). Drying conditions were optimized by using the response surface methodology. 13 experiments were carried out considering incident microwave powers from 285 to 795 W, air temperature from 46 to 74 ºC and slice thickness from 1.2 to 6.8 mm.